Courseware on e-solat in mobile - Syaifudin, Ramzan (2010)
The modern technology has change the way of many people work, studies and learning. People concentrate on their work but they ignore their real responsibility to their children which is teach and grown them. The course that children must learn from they are kids are so/at which the basic learn on how to be good Muslim. Many of teenager nowadays are always not doing so/at went the time is come because lack of knowledge on how to so/at and lack practice of so/at in daily life. Courseware on ESo/at is developing to guide user especially kid around six to twelve years old on how to doing so/at. This courseware divides into two main courses which is learning so/at and learning and remembering short surah. Under so/at, there are five option which is kids can choose which so/at he or she want to learn. The options are So/at Subuh, So/at Zohor, So/at Asar, So/at Magrib and So/at Isya'. The animation will teach kids how to so/at.